Effect of encapsulation technology and in vitro digestion on the hypocholesterolemic activity of Limosilactobacillus fermentum K73 - Cardoso-Cardenas, Mary; Bauer-Estrada, Katherine; Diaz-Barrera, Luis Eduardo; Quintanilla-Carvajal, Maria Ximena (Frontiers in Microbiology, 2025)
IntroductionMembers of the Lactobacillaceae family have been extensively investigated for their health-promoting properties, including the restoration of cellular functions, inhibition of pathogen colonization, and cholesterol-lowering effects.MethodologyThis study evaluated the hypocholesterolemic activity of Limosilactobacillus fermentum K73 at various stages of encapsulation using three distinct capsule types, including simulated gastrointestinal (GI) transit and analysis of adhesion to HT-29 and RKO intestinal epithelial cells.ResultsThe strain demonstrated a pronounced ability to deconjugate taurine-conjugated bile salts, particularly taurocholic acid sodium (TCA) and sodium taurodeoxycholate acid (TDCA), as evidenced by viable cell counts. In bioreactor samples, counts reached 8.31 and 7.82 log CFU/mL for TCA and TDCA, respectively. After capsule dissolution, viability decreased across all formulations: C1 showed 6.90 and 5.04, C2 reached 4.99 and 4.68, and C3 recorded 6.10 and 4.12 log CFU/mL. Following in vitro digestion, C1 exhibited notable recovery, with 7.30 log CFU/mL (TCA) and 4.26 log CFU/mL (TDCA). Cholesterol absorption was highest in digested C1 (65.49%), surpassing the 24-h broth culture (63.9%). Adhesion to epithelial cells varied by formulation; for HT-29 cells, C1, C2, and C3 showed 21, 5, and 33 adhered bacteria, respectively, while for RKO cells, adhesion was 44 (C1), 22 (C2), and 201 (C3).DiscussionThese findings demonstrate that L. fermentum K73 maintained its viability, hypocholesterolemic activity, and epithelial adhesion capacity throughout encapsulation and simulated GI digestion, supporting its potential application as a functional probiotic strain in nutraceutical and food products.